Isolated Central Nervous System Relapse Following Treatment Reduction in Low-risk Acute Lymphoblastic Leukemia at the Children's Cancer Center of Lebanon. Issue 6 (August 2020) - El-Khoury, Habib; Chahrour, Mohamad; Ghanem, Khaled M.; Saifi, Omran; Tamim, Hani; El-Solh, Hassan; Hamideh, Dima; Tarek, Nidale; Saab, Raya; Abboud, Miguel R.; Muwakkit, Samar A.
Abstract : The aim of this trial was to decrease the incidence of life-threatening infections by decreasing the dose and the duration of dexamethasone treatment during maintenance therapy. This was a prospective, nonrandomized trial of low-risk acute lymphoblastic leukemia patients 1 to 18 years of age who were treated at the Children's Cancer Center of Lebanon (CCCL). Patients consecutively diagnosed between 2002 and 2013 were divided into groups 1 and 2 receiving total dexamethasone doses of 1144 and 618 mg/m 2, respectively. A total of 84 patients were assigned to group 1 and 33 patients to group 2. The 5-year cumulative incidence of isolated central nervous system relapse increased from (n=0% [95% confidence interval: 0%-4.4%]) in group 1 to 9.1% [95% confidence interval: 3%-23%]; P =0.021) in group 2. Decreasing cumulative dose of dexamethasone for low-risk childhood acute lymphoblastic leukemia patients aiming to avoid serious viral infections led to a significant increase in isolated central nervous system relapse.